Quantitative Evaluations of Time‐Course and Treatment Effects of Systemic Agents for Psoriasis: A Model‐Based Meta‐Analysis. Issue 6 (21st June 2017) - Checchio, T; Ahadieh, S; Gupta, P; Mandema, J; Puig, L; Wolk, R; Valdez, H; Tan, H; Krishnaswami, S; Tallman, A; Kaur, M; Ito, K
Abstract : Aggregate data model‐based meta‐analysis is a regression approach to compare the dose–response and/or time‐course across different treatments using summary level data from the literature. Literature search and systematic review following the Cochrane approach yielded 912 sources for investigational and approved treatments for psoriasis. In addition, data for tofacitinib were obtained from an internal database. Tofacitinib is an oral Janus kinase inhibitor. Two mathematical models were developed for Psoriasis Area and Severity Index (PASI) response in moderate to severe psoriasis patients to quantify the time to maximum effect for PASI75 and to evaluate the dose–response relationship for PASI responders (PASI50, PASI75, PASI90, PASI100) at Week 12. Body weight exhibited an inverse effect on the placebo component of both models, suggesting that body weight affects the overall PASI response regardless of drug. This analysis provides a quantitative framework for efficacy comparisons across psoriasis treatments.